Efektifitas penggunaan bingkai jaring pada penjarangan benih kerang mutiara, Pinctada maxima - Tomatala, Pitjont (e-Journal BUDIDAYA PERAIRAN, 2014)
Abstract Pearl oyster Pinctada maxima is  one of the sea resource that has an economic value in national and international market.  Recently, many companies  have succeeded in producing hundreds of  thousand spat through hatchery. However,  mortality rate of spat in rearing activityies in the sea was remain high. It was caused by unfavorable handling of spat during the spacing process. The purpose of this research was evaluate the effectiveness of using frame net in spat handling at spacing process. This research was conducted at Luv Bay of Tual City, Maluku Province on March to April 2012. The observation was conducted to measure the shell growth and survaival of  P. maxima spat. The result suggested that the use of frame net in the spacing  process of pearl oyster had great advantage. It was proven by the normal growth and high survival rate.   Keywords : Pinctada maxima, spat, growth rate, survaival rate